Model Pembelajaran Bahasa Arab Multiliterasi Berbasis Kearifan Lokal Dan Moderasi Islam di Perguruan Tinggi Negeri - Andy Hadiyanto; Siti Maria Ulfah; Cendra Samitri (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2020)
This study aims to develop a multiliteration of Arabic language learning based on local wisdom in public universities that are valid, effective, efficient, and practical so that it can be used as an alternative to other learning models applied by Arabic lecturers. This study uses a qualitative approach with the pattern "the dominantless dominant design" and research and development (R&D) research design. The research was conducted in two stages: (1) a preliminary study (exploratory study), and (2) development of a model (Action Research. Collecting data through interviews, observations, documentation, questionnaires (tests), and FGDs. The results showed: 1) learning Arabic is too behavioristic and only produces mechanistic language skills, 2) Multiliterated Arabic learning must enable students to carry out the process of intensification and extensification of their ability to communicate using Arabic so as to develop their abilities and communication skills using language Arabic independently by using multiple sources and media, 3) multiliterated Arabic learning that places students in the context of real life must be accompanied by understanding and awareness of the importance of the integration of Indonesian local wisdom in the learning process, 4) Components and syntax of multiliterated Arabic learning models based on Local wisdom refers to empirical and theoretical findings, namely objectives, methods, materials and evaluation of learning.